Pengaruh Pengetahuan Investasi, Kemampuan Finansial Dan Lingkungan Pertemanan Terhadap Minat Investasi Mahasiswa (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2021) - Anisa Putri Darvanti; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of investment knowledge, financial capability and friendship environment on investment interest in UNISMA. The type of research used is quantitative. Samples taken using purposive sampling technique with Malhotra formula, That is the number of indicators x 5 so that the total sample is 85 respondents. The data analysis method used is multiple linear regression analysis. It uses the F Test for simultaneous hypothesis testing and the t Test for partial testing. In this study, the results obtained are Investment knowledge, financial ability and friendship environment simultaneously affect investment interest. Investment knowledge does not have a partial effect on investment interest, financial ability has a partial effect on investment interest and the friendship environment has a partial effect on investment interest. Keywords: Investment Knowledge, Financial Capability, Friendship Environment, Multiple Linear Regression, Purposive Sampling